Analisis Pertimbangan Hukum Hakim dalam Penetapan Pengadilan Agama Nomor 190/Pdt.P/Pa.Smg - Nofiana, Iska (Al-Hukkam: Journal of Islamic Family Law, 2025)
Islamic inheritance law explains that heirs can be prevented from receiving inheritance if they are involved in a murder case, have a different religion from the testator, and because of slavery. In terms of normative juridical terms, the Supreme Court explains that nonmuslim relatives are prevented from inheriting property from a Muslim testator, but can still obtain their rights because they are blood relatives of the testator. Based on the background of the problem in writing this thesis, this study has the following problem formulation: (1) What are the legal considerations of the judge in the determination of Number 190/Pdt.P/2019/PA. Smg regarding nonmuslim heirs who are not given a mandatory will? (2) What are the legal consequences of the determination of No. 190/Pdt.P/2019/PA.Smg which does not follow the Supreme Court's jurisprudence regarding the granting of mandatory wills to nonmuslim heirs? The methodology used is qualitative research using a normative juridical approach. This study discusses the analysis of one of the court products in the form of a judge's decision not to grant a mandatory will to nonmuslim heirs. The judge considered based on Islamic law sources and facts in the trial. However, the Panel of Judges did not include the legal basis derived from the Supreme Court's Jurisprudence on mandatory wills for nonmuslim heirs.